"When you leave your country, this is what you're in for": experiences of structural, legal, and gender-based violence among asylum-seeking women at the Mexico-U.S. border - Kaylee Ramage; Emma Stirling-Cameron; Nicole Elizabeth Ramos; Isela Martinez SanRoman; Ietza Bojorquez; Arianna Spata; Brigitte Baltazar Lujano; Shira M. Goldenberg (BMC, 2023)
Abstract Background Recent U.S. immigration policy has increasingly focused on asylum deterrence and has been used extensively to rapidly deport and deter asylum-seekers, leaving thousands of would-be asylum-seekers waiting indefinitely in Mexican border cities, a large and growing proportion of whom are pregnant and parenting women. In the border city of Tijuana, Mexico, these women are spending unprecedented durations waiting under unsafe humanitarian conditions to seek safety in the U.S, with rising concerns regarding increases in gender-based violence (GBV) among this population during the COVID-19 pandemic. Given existing gaps in evidence, we aimed to describe the lived experiences of GBV in the context of asylum deterrence policies among pregnant and parenting asylum-seeking women at the Mexico-U.S. border. Methods Within the community-based Maternal and Infant Health for Refugee & Asylum-Seeking Women (MIHRA) study, we conducted semi-structured qualitative interviews with 30 asylum-seeking women in Tijuana, Mexico between June and December 2022. Eligible women had been pregnant or postpartum since March 2020, were 18-49 years old, and migrated for the purposes of seeking asylum in the U.S. Drawing on conceptualizations of structural and legal violence, we conducted a thematic analysis of participants' experiences of GBV in the context of asylum deterrence policies and COVID-19. Results Pregnant and parenting asylum-seeking women routinely faced multiple forms of GBV perpetuated by asylum deterrence policies at all stages of migration (pre-migration, in transit, and in Tijuana). Indefinite wait times to cross the border and inadequate/unsafe shelter exacerbated further vulnerability to GBV. Repeated exposure to GBV contributed to poor mental health among women who reported feelings of fear, isolation, despair, shame, and anxiety. The lack of supports and legal recourse related to GBV in Tijuana highlighted the impact of asylum deterrence policies on this ongoing humanitarian crisis. Conclusion Asylum deterrence policies undermine the health and safety of pregnant and parenting asylum-seeking women at the Mexico-U.S. border. There is an urgent need to end U.S. asylum deterrence policies and to provide respectful, appropriate, and adequately resourced humanitarian supports to pregnant and parenting asylum-seeking women in border cities, to reduce women's risk of GBV and trauma.